Suppose that: (x-(x-y))-((x-y)-x)=14 what is x
1 answer:
Answer:
x = 0.
Step-by-step explanation:
(x-(x-y))-((x-y)-x)=14
Remove the parentheses from the inside out:
(x - x + y) - (x - y - x) = 14
x - x + y - x + y + x = 14
x - x - x + x + 2y = 14
0 + 2y = 14
x = 0 and y = 7.
You might be interested in
Answer:
7
Step-by-step explanation:
31 Wings (already cooked)
+ 32 Wings (started cooking)
= 63 Wings total
divided by 9 customers
= 7 per person
Answer:
2/6
Step-by-step explanation:
because 4/6 is eaten so that means 2/6 is left to eat
All you have to do is substitute x for 3.
You get:
14.50 times 3
14.50 times 3 is 43.50
The answer is $14.50
Is this Dolli Buchannan Its Alexis!!!!
Answers:
1) 6
2) 5
3) 8
4)5ab^5